Moderately Reducing Nitrogen Application Ameliorates Salt-Induced Growth and Physiological Damage on Forage Bermudagrass - Shao, An; Wang, Hongli; Xu, Xiao; Li, Xiaoning; Amombo, Erick; Fu, Jinmin (Frontiers in Plant Science, 2022)
Nitrogen (N) application is one of the most effective methods to alleviate salt-induced damage on plants. Forage bermudagrass has higher utilization potential on saline soil, but whether its N requirement changed under high salt stress has not been studied. Through examining plant-growth related traits, salt-stress responsive physiological traits, photosynthesis, N metabolism and forage quality supplied with different N concentration under high salt stress (200 mM NaCl), we noticed that optimum N requirement of forage bermudagrass reduced. When supplied with 10 mM N under higher salt stress, plants had the similar biomass, turf color, chlorophyll content with plants supplied with 15 mM N, accompanied with lower firing rate and Na+ content of leaves. The N content, crude protein, crude fat content, the expression of AMT (Ammonium Transporters), NR (Nitrate Reductase), GS (Glutamine Synthetase) and GOGAT (Glutamate Synthetase), the chlorophyll fluorescence curve and parameters of leaves (e.g. PIABS; PICS; ABS/RC; TRo/RC; ETo/RC) all peaked under 10 mM N under high salt stress instead of 15 mM N. Through exploring the proper N application under higher salt stress and its alleviation mechanisms, our results indicated that moderate reduction of N application under high salt level had a maximum promotion effect on the salt tolerance of forage bermudagrass without growth or forage quality inhibition. These response mechanisms obtained can provide useful reference for N application in moderation rather than in excess on forage bermudagrass especially in higher salinity areas.